1-Diphenylphosphanyl-2-(diphenylphosphoryl)hydrazine - Martha Höhne; Bhaskar R. Aluri; Anke Spannenberg; Bernd H. Müller; Normen Peulecke; Uwe Rosenthal (IUCrData, 2018)
The title compound, C24H22N2OP2, is an asymmetrically substituted hydrazine derivative bearing a phosphoryl and a phosphanyl substituent. The PNNP backbone has a torsion angle of −131.01 (8)°. In the crystal, molecules form centrosymmetric dimers by intermolecular N—H...O hydrogen bonds, which are further linked into a three-dimensional network by weak C—H...O and C—H...π interactions.